2021
DOI: 10.1002/ana.26199
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic and Pallidal Stimulations in Patients with Parkinson's Disease: Common and Dissociable Connections

Abstract: Objective: The subthalamic nucleus (STN) and internal globus pallidus (GPi) are the most effective targets in deep brain stimulation (DBS) for Parkinson's disease (PD). However, the common and specific effects on brain connectivity of stimulating the 2 nuclei remain unclear. Methods: Patients with PD receiving STN-DBS (n = 27, 6 women, mean age 64.8 years) or GPi-DBS (n = 28, 13 women, mean age 64.6 years) were recruited for resting-state functional magnetic resonance imaging to assess the effects of STN-DBS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In addition, the relationship between dopaminergic depletion and thalamocortical hyperconnectivity is in line with recent data indicating that deep brain stimulation, targeting either the globus pallidus pars interna or the subthalamic nucleus, decreases the FC of the thalamus with the somatosensory-motor cortices 29 . Indeed, hyperactivity of the internal pallidus and subthalamic nucleus is a well-known net effect of the loss of inhibitory nigrostriatal projections in PD.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the relationship between dopaminergic depletion and thalamocortical hyperconnectivity is in line with recent data indicating that deep brain stimulation, targeting either the globus pallidus pars interna or the subthalamic nucleus, decreases the FC of the thalamus with the somatosensory-motor cortices 29 . Indeed, hyperactivity of the internal pallidus and subthalamic nucleus is a well-known net effect of the loss of inhibitory nigrostriatal projections in PD.…”
Section: Discussionsupporting
confidence: 88%
“…In a resting-state functional MRI (rs-fMRI) study of depression by Wen and colleagues, compared to healthy controls, patients with PD were found to have increased neural activity in prefrontal regions and decreased functional connectivity between prefrontal and limbic structures [ 35 ]. Research has demonstrated that STN-DBS influences the connectivity among the motor-associated cortex, thalamus, and cerebellum, thereby suggesting that structures influenced by STN-DBS are partly associated with areas involved in depression [ 36 , 37 ]. In contrast, studies have shown that changes in glucose metabolism induced by STN-DBS affect the levels of ketamine, which has rapid antidepressant and anti-anhedonic effects in brain structures [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cs-fMRI study, Dimarzio et al found that GPi-DBS (n ¼ 3 subjects) was associated with significantly more primary motor cortex activation than STN-DBS (n ¼ 4 subjects) [27]. Further, a recent rs-fMRI study found that while STN-DBS and GPi-DBS were both associated with significant changes in thalamo-cortical and cortico-cerebellar functional connectivity, STN-DBS was associated with more widespread functional connectivity changes than GPi-DBS, including between somato-motor and visual regions [73]. A third study included subjects with both GPi-and STN-DBS, however, the authors did not directly compare fMRI responses between groups [25].…”
Section: Parkinson's Diseasementioning
confidence: 95%